Formulation and Evaluation of a New Biodegradable Periodontal Chip Containing Thymoquinone in a Chitosan Base for the Management of Chronic Periodontitis. (31st March 2013) - Al-Bayaty, Fouad H.; Kamaruddin, Azwin A.; Ismail, Mohd. A.; Abdulla, Mahmood A.
Abstract : Objective. This study was performed to develop a biodegradable periodontal chip containing thymoquinone and to evaluate its effectiveness for managing chronic periodontitis. Methods. Chips were formulated from thymoquinone and chitosan. Twelve patients with periodontal pockets measuring ≥5 mm participated in this study. Overall, 180 periodontal pockets were evaluated. At day zero, all patients were treated with full-mouth scaling and root planning. Periodontal pockets were divided into three groups. Group one served as the control group, while group two received plain chitosan chips. Group three received chips containing thymoquinone. Plaque index, bleeding upon probing, periodontal probing pocket depths, and clinical attachment levels were recorded at days 0 and 60. Results. The statistical significance of differences was tested with a paired sample t -test, a Chi-squared test, and a one-way ANOVA. The results indicated significant improvement in plaque index and bleeding upon probing and a reduction in periodontal pockets from baseline in all four groups ( P < 0.05 ) . Gains in clinical attachment levels were significantly higher ( P < 0.005 ) in the group receiving thymoquinone chips compared to other groups. Conclusion. Periodontal chips containing thymoquinone can be used as adjuncts for the treatment of patients with chronic periodontitis.